2022
DOI: 10.3390/ijerph191610007
|View full text |Cite
|
Sign up to set email alerts
|

Are Crohn’s Disease Patients Limited in Sport Practise? An UltraEndurance Case–Control Study Response

Abstract: The aim of this study was to analyze the psychophysiological response of a Crohn’s Disease patient in an ultra-endurance event. The psychophysiological responses of a Crohn’s Disease and non-Crohn’s Disease participant were analysed before during and after an 8 h ultra-endurance running event. Results showed how Crohn’s patient presented a similar psychophysiological response than non-Crohn’s participant in the ultra-endurance event, except for a higher pre- and post-event sympathetic modulation, lower event s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…This means that once the diagnosis is made, we will have these people in follow-up consultations, check-ups, and pharmacology throughout life, which is associated with high healthcare costs during this process [ 374 , 375 , 376 , 377 , 378 , 379 , 380 ]. In addition, in these diseases, we must consider that there will be moments of remission, but also episodes in which the symptomatology worsens significantly during outbreaks [ 381 , 382 , 383 ].…”
Section: Sanitary Costs Of Western Dietmentioning
confidence: 99%
“…This means that once the diagnosis is made, we will have these people in follow-up consultations, check-ups, and pharmacology throughout life, which is associated with high healthcare costs during this process [ 374 , 375 , 376 , 377 , 378 , 379 , 380 ]. In addition, in these diseases, we must consider that there will be moments of remission, but also episodes in which the symptomatology worsens significantly during outbreaks [ 381 , 382 , 383 ].…”
Section: Sanitary Costs Of Western Dietmentioning
confidence: 99%
“…The sports activity is a barrier for patients with active Crohn’s disease (intestinal manifestations) because it flares up the symptoms[ 15 ]. Some authors believe that the barriers to sports medicine are related to psychosocial factors and alterations in the physiological responses to exercise, characterized by a lower sympathetic tone and body temperature[ 16 ]. In the scoping review, which included 28 articles, the authors recommended that moderately intense PA is a useful non-pharmacological intervention to improve the quality of life and attenuate the activity of Crohn’s disease[ 17 ].…”
Section: To the Editormentioning
confidence: 99%
“…22–24 However, it is noted that some case studies have raised some objections that exercise during the active phase may aggravate the condition of patients with IBD. 25 26 It is worth mentioning that exacerbation may be related to the intensity or frequency of exercise. It has been found that prolonged strenuous exercise may lead to multiple physiological changes related to hypoperfusion and ischaemia, altered gastrointestinal motility, and local and systemic inflammation, which may result in gastrointestinal syndromes induced by acute disturbances in gastrointestinal health.…”
Section: Introductionmentioning
confidence: 99%